The 'Welcomed Lockdown' Hypothesis: When Do Mobility Restrictions Influence Mental Wellbeing? - Joan Costa-i-Font; Martin Knapp; Cristina Vilaplana-Prieto (Center for Economic Studies and ifo Institute (CESifo), 2022)
The COVID-19 pandemic and its mobility restrictions have been an external shock, influencing wellbeing. However, does risk exposure affect the welfare effect of lockdowns? This paper examines the 'welcomed lockdown' hypothesis, namely the extent to which there is a level of risk where mobility restrictions are not a hindrance to wellbeing. We exploit the differential timing of the effect of the pandemic across European countries, and the different stringency of lockdown to examine the effects on two mental health conditions, namely anxiety and depression. We examine whether differences in symptoms of anxiety and depression are explained by mortality and stringency of lockdown measures using ad event study that draws on Coarsened Exact Matching (CEM), Difference-in-Difference (DiD) and Regression Discontinuity Design (RDD). Our estimates suggest an average increase in depression (3.95%) and anxiety (10%) symptoms relative to the mean level on the day that the lockdown took effect. However, such effects are wiped out when a country exhibits high mortality ('pandemic category 5'). Hence, we conclude that in an environment of high mortality, lockdowns no longer give rise to a reduction in well-being consistent with the 'welcome lockdown' hypothesis.
Keywords: I18; 330; anxiety; depression; Covid-19; pandemic; lockdown